Kamingaw an impressionist portrait of the Bisaya painter Martino A. Abellana - Fernandez, Raymund Lozada 1955- (University of San Carlos Press, 2017)
"This book presents, like an Impressionist painting, a portrait of the man, Martino Alcoseba Abellana: what he was like, what he believed in, what he did, and who he was. This bold task is best done with broad strokes; hopefully, to produce in the end what can only be a fleeting impression. This is not a book of history. An historic biography would be quite useful. But histories sometimes miss things that are easier apprehended by way of a more literary approach. This is the spirit that guides this writing..."-- Provided by publisher